Elementary Linear Algebra : A Matrix Approach - Spence, Lawrence E (Pearson Education, 2008)
This book is written for a matrix-oriented course, as recommended by the Linear Algebra Curriculum Study Group. It begin with the sudy of matrices, vectors, and systems of linear equations and gradually leads to more complicated concepts and general principles, such as linear independence, subspaces, and bases. This book, also, includes a wide variety of applications, and they are given when the necessary prerequisites have been introduced. There are applications to economics, electrical networks, population change, traffic flow, scheduling, anthropology, google searhes, counting problems, predator-prey models and harmonic motion, least squares approximation, computer graphics, pricipal component analysis, and music.